Review of gait, cognition, and fall risks with implications for fall prevention in older adults with Dementia - Zhang, Weihong; Schwenk, Michael (Dementia and geriatric cognitive disorders, 2019)
Background: Older people with cognitive impairment are at increased risk of falls; however, fall prevention strategies have limited success in this population. The aim of this paper is to review the literature to inform a theoretical framework for fall prevention in older adults with dementia. Summary: A narrative review was conducted on fall risk factors in people with cognitive impairment, the relationship between cognition and gait, and their joint impact on the risk of falls. This was used to develop a theoretical framework for fall prevention for people with dementia. Executive function and motor function are closely related as they share neuroanatomy. This close relationship has been confirmed by observational studies including neuroimaging and intervention studies. Executive function is the cognitive domain most commonly associated with gait dysfunction. Attention, sensory integration, and motor planning are the sub-domains of executive function associated with risk of falls through gait dysfunction, whereas cognitive flexibility, judgement, and inhibitory control affect risk of falls through risk-taking behaviour. Key Messages: Gait, cognition, and falls are closely related. The comorbidity and interaction between gait abnormality and cognitive impairment may underpin the high prevalence of falls in older adults with dementia. Gait assessment and cognitive assessment, particularly executive function, should be integrated in fall risk screening. Assessment results should be interpreted and utilised using a multidisciplinary approach; specific strategies such as customised gait training and behavioural modulation should be considered as part of falls prevention for people with dementia.
Gesehen am 19.02.2020